2011
DOI: 10.2105/ajph.2010.200162
|View full text |Cite
|
Sign up to set email alerts
|

The Social Marketing of Safety Behaviors: A Quasi–Randomized Controlled Trial of Tractor Retrofitting Incentives

Abstract: Our results showed that a social marketing approach (financial incentives, tailored messages, and promotion) had the greatest influence on message recall, readiness to retrofit tractors, and intentions to retrofit tractors and that behavioral measures were fairly good predictors of tractor retrofitting behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…As a result, selection of participants was based on the following criteria: The New York State ROPS Rebate Program Hotline is part of a social marketing intervention in New York that provides financial and logistical assistance for installing ROPS and promotional messages/ materials encouraging ROPS installation. 18,19 Thus interest in retrofitting was based on an individual having called the hotline to inquire about ROPS for their tractor.…”
Section: Focus Group Discussionmentioning
confidence: 99%
“…As a result, selection of participants was based on the following criteria: The New York State ROPS Rebate Program Hotline is part of a social marketing intervention in New York that provides financial and logistical assistance for installing ROPS and promotional messages/ materials encouraging ROPS installation. 18,19 Thus interest in retrofitting was based on an individual having called the hotline to inquire about ROPS for their tractor.…”
Section: Focus Group Discussionmentioning
confidence: 99%
“…2,7 The research into motivating farmers to retrofit older tractors with rollover protective structures (ROPS) helps explain how barriers and motivating factors are not two sides of the same coin. For example, Sorensen and colleagues, 8 building upon the work of Hallman,9 found that because you address major barriers to ROPS retrofitting such as financial costs and time constraints, you don't necessarily achieve the best intervention results. In Sorensen et al's 8 research, they found the greatest change in farmers' intentions to install ROPS came from farmers exposed to a rebate (addressed barrier to behavioral change) and a targeted promotional campaign (addressed motivating factors for behavioral change), compared with farmers who received generic promotional pieces and a rebate incentive (barrier to behavioral change), farmers who received only targeted promotional campaign (addressed motivational factors), or a control group (no rebates or promotional campaign).…”
Section: Barriers Versus Motivatorsmentioning
confidence: 99%
“…For example, in the case of ROPS retrofitting, adult tractor operators did not identify self-protection as a barrier or a motivator. 8 All this information, then, can be used to develop intervention strategies and programs that facilitate adoption of the recommended practice.…”
Section: Barriers Versus Motivatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…All indicators are that this somewhat cowardly approach to optimistic bias has proven to be effective. 10 Optimistic bias is a very common and quite robust phenomenon that can significantly impact efforts to change behavior. To a large degree it explains the quite limited impact of education as an intervention.…”
mentioning
confidence: 99%